2021
DOI: 10.5858/arpa.2020-0457-oa
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clonotypic Rearrangements and Minimal Residual Disease in Lymphoid Malignancies

Abstract: Context.— Measurable (minimal) residual disease (MRD) is an independent prognostic factor for survival outcomes in patients with lymphoid and plasma cell malignancies and has been incorporated into consensus criteria regarding treatment response, strategy, and clinical trial endpoints. clonoSEQ (a next-generation sequencing [NGS]-MRD assay) uses multiplex polymerase chain reaction and NGS to identify clonotypic rearrangements at the immunoglobulin (Ig) H, IgK, IgL, T-cell receptor (TCR)-β, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…In the same study, malignant T cells could be isolated from the blood of patients with new skin lesions but no clinical involvement of the peripheral blood, highlighting that early blood involvement may be detected by HTS. Numerous other studies have demonstrated that HTS has superior sensitivity and/or specificity as compared to PCR for detection of malignant cells in the skin and or blood ( 35 38 ).…”
Section: Diagnostic and Prognostic Evaluation Of Ctclmentioning
confidence: 99%
“…In the same study, malignant T cells could be isolated from the blood of patients with new skin lesions but no clinical involvement of the peripheral blood, highlighting that early blood involvement may be detected by HTS. Numerous other studies have demonstrated that HTS has superior sensitivity and/or specificity as compared to PCR for detection of malignant cells in the skin and or blood ( 35 38 ).…”
Section: Diagnostic and Prognostic Evaluation Of Ctclmentioning
confidence: 99%
“…ScRNA analysis can also be used to identify multi-functional responding cells (35, 36). TCR sequencing focuses on the antigen receptors expressed by T cells and has been used for diagnosis and personalized monitoring of remission and relapse in multiple hematologic cancers (32,37). At the population level, TCR sequencing has been used to determine the clonality and repertoire dynamics of public T cell responses (38, 39).…”
Section: Molecular Immune Monitoring Assays Currently Used In Clinica...mentioning
confidence: 99%
“…Potentially clinically relevant applications of cfDNA involve the detection of minimal residual disease (MRD) to monitor therapy response, as has been applied in different lymphoma types [80,81], including cHL [50,82], and for prognostic stratification [14,52,[82][83][84][85]. This requires sensitive NGS-based assays, such as ClonoSEQ (formerly known as Lym-phoSIGHT) [81,86], CAPP-Seq [87], PhasED-Seq [88], or the EuroClonality-NGS DNA capture (EuroClonality-NDC) assay [89].…”
Section: New Developments In Molecular Testing Of Classical Hodgkin L...mentioning
confidence: 99%